Coal water slurry additive

By using a water-coal slurry additive consisting of a main dispersant and an auxiliary stabilizer, the problems of insufficient dispersibility and poor stability in the existing water-coal slurry system are solved, and efficient dispersion and improved stability of the water-coal slurry are achieved.

CN120624086APending Publication Date: 2025-09-12ANHUI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510980798.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-16
Publication Date
2025-09-12

AI Technical Summary

Technical Problem

The existing water-coal slurry system has problems of insufficient dispersibility and poor stability, and the existing additive components are single and the synergistic effect is weak.

Method used

A water-coal slurry additive consisting of a main dispersant and an auxiliary stabilizer is used. The main dispersant is polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, and the auxiliary stabilizer is an oxidation-hydroxymethylation modified complex of lignin sulfonate and sodium humate. The two are synergistically matched to improve dispersibility and stability.

Benefits of technology

It significantly improves the dispersibility and stability of water-coal slurry, enhances the rheological properties and storage stability, and provides technical support for the efficient application of water-coal slurry.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005502871760000091
    Figure BDA0005502871760000091
  • Figure BDA0005502871760000101
    Figure BDA0005502871760000101
  • Figure BDA0005502871760000102
    Figure BDA0005502871760000102
Patent Text Reader

Abstract

The invention relates to the technical field of coal water slurry, in particular to a coal water slurry additive which comprises a main dispersant and an auxiliary stabilizer, the main dispersing agent is a polystyrene-maleic anhydride grafted sulfonated acetone-phenol polycondensate, and the auxiliary stabilizer is an oxidation-hydroxymethylation modified compound of lignosulfonate and sodium humate. The coal water slurry additive comprises the main dispersing agent and the auxiliary stabilizer, and the main dispersing agent and the auxiliary stabilizer act together, so that the coal water slurry additive has the advantages that the coal water slurry additive is uniform in dispersion and high in stability; and the action effect of the additive in the coal water slurry is improved. The main dispersing agent is polystyrene-maleic anhydride grafted sulfonated acetone-phenol polycondensate, and sulfonated acetone-phenol polycondensate chain segments: sulfonic acid groups introduced after phenol is sulfonated can generate strong negative charges through ionization, and the strong negative charges and positive charges on the surfaces of pulverized coal particles form electrostatic repulsion, so that the agglomeration force among the particles is remarkably reduced; a net structure formed by crosslinking acetone and formaldehyde endows molecular chains with certain rigidity, so that the molecular chains form a stable adsorption layer on the surfaces of particles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coal-water slurry, in particular to a coal-water slurry additive. Background Art

[0002] Coal-water slurry is a liquid-solid two-phase fluid composed of pulverized coal, water, and a small amount of additives. It has the characteristics of high combustion efficiency, low pollution emissions, and convenient transportation and storage. It is widely regarded as a clean and efficient fuel to replace traditional coal. Its preparation principle is to evenly disperse pulverized coal in water to form a stable system with good fluidity. Against the backdrop of energy structure transformation and increasingly stringent environmental protection requirements, the demand for the application of coal-water slurry in industrial boilers, power plant combustion and other fields continues to grow. Additives are the core components for regulating the performance of coal-water slurry, and their performance directly determines the application effect of coal-water slurry.

[0003] The existing water-coal slurry system generally has three major technical problems: insufficient dispersibility and poor stability.

[0004] In addition, some additives in the existing technology have the defects of single components and weak synergistic effects. The water-coal slurry additive provided by the invention breaks through the traditional technical path from the molecular design level through the synergistic ratio of the main dispersant and the auxiliary stabilizer. The grafted structure and sulfonated group of the main dispersant can enhance the adsorption and dispersion ability of coal powder particles, and the modified group of the auxiliary stabilizer can maintain the stability of the system through electrostatic repulsion and steric hindrance. The combination of the two can significantly improve the dispersibility and stability performance of water-coal slurry, providing a technical solution for the efficient application of water-coal slurry. Summary of the Invention

[0005] The purpose of the present invention is to provide a coal water slurry additive, which can significantly improve the dispersibility, stability and rheological properties of coal water slurry and provide a technical solution for the efficient application of coal water slurry.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A coal water slurry additive consists of a main dispersant and an auxiliary stabilizer; the main dispersant is a polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensate, the auxiliary stabilizer is an oxidation-hydroxymethylation modified complex of lignin sulfonate and sodium humate, and the mass ratio of the main dispersant to the auxiliary stabilizer is 1:(0.25-0.45).

[0008] Preferably, in the polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, the sulfonated acetone-phenol condensation polymer is prepared by reacting phenol, acetone, and formaldehyde, the molar ratio of the phenol, acetone, and formaldehyde is 1:(0.9-1.1):(2.1-2.4), and the phenol is pre-sulfonated with concentrated sulfuric acid, with a sulfonation degree of 62%-68%. The weight-average molecular weight of the sulfonated acetone-phenol condensation polymer is 8500-11500 Da.

[0009] Preferably, the preparation method of the sulfonated acetone-phenol condensation polymer comprises: condensing acetone and sulfonated phenol at 42-48° C. for 1.5 hours to generate a linear prepolymer; heating to 87-93° C., adding formaldehyde to carry out a cross-linking reaction for 2 hours, wherein the pH value of the reaction system is 9.2-9.8; terminating the reaction by adding sodium bisulfite, a reaction terminator, in an amount of 0.6%-0.9% by weight of the total mass of the reaction system; and finally filtering, washing, and drying to obtain the product.

[0010] Preferably, in the polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, the polystyrene-maleic anhydride copolymer is prepared by free radical copolymerization of styrene and maleic anhydride, the molar ratio of styrene to maleic anhydride is 3:1, the reaction is carried out in a toluene solvent accounting for 55%-65% of the total mass of the reaction system, the initiator is benzoyl peroxide, the amount used is 1.3%-1.7% of the total mass of styrene and maleic anhydride, and the reaction temperature is 71-74°C.

[0011] Preferably, the polystyrene-maleic anhydride copolymer needs to be subjected to chlorination treatment to convert 42%-48% of the carboxyl groups in the copolymer into chlorinated groups.

[0012] Preferably, in the polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, the mass ratio of sulfonated acetone-phenol condensation polymer to polystyrene-maleic anhydride is 1:(0.35-0.45), and in the aprotic solvent N,N-dimethylformamide, a zinc-aluminum composite oxide is used as a bimetallic catalyst to catalyze the condensation of the hydroxyl-terminated sulfonated acetone-phenol condensation polymer with the acyl chloride group, and the amount of the zinc-aluminum composite oxide is 0.9-1.1wt% of the total mass of the sulfonated acetone-phenol condensation polymer and the polystyrene-maleic anhydride.

[0013] Preferably, the grafting reaction temperature is 110-114° C., and the reaction time is 4.0-4.8 hours.

[0014] Preferably, the preparation method of the auxiliary stabilizer comprises:

[0015] Mechanical activation step: lignin sulfonate and sodium humate are mixed and crushed by a high-speed airflow mill to make the mixed material particle size ≤5μm;

[0016] Oxidation modification step: placing the mechanically activated material in an alkaline environment, adjusting the system pH to 10-11, introducing ozone for oxidation reaction, and controlling the oxidation degree at 15%-18%;

[0017] Hydroxymethylation reaction step: add formaldehyde accounting for 8%-10% of the weight of lignin to the material after oxidative modification, react at 62-68° C. for 1 hour, filter and wash to neutrality, and dry to obtain an auxiliary stabilizer.

[0018] Preferably, in the auxiliary stabilizer, the mass ratio of lignin sulfonate to sodium humate is 3:1.

[0019] Compared with the prior art, the present invention has the following beneficial effects:

[0020] 1. The water-coal slurry additive of the present invention is composed of a main dispersant and an auxiliary stabilizer. The two work synergistically to greatly improve the efficacy in water-coal slurry. The main dispersant is polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer. In the sulfonated acetone-phenol condensation polymer chain segment, the sulfonic acid group introduced by phenol sulfonation ionizes to produce a strong negative charge, which electrostatically repels the positive charge on the surface of the coal powder particles, reducing the agglomeration force; the network structure cross-linked by acetone and formaldehyde gives the molecular chain rigidity, forming a stable adsorption layer on the particle surface, enhancing the dispersion stability. In the polystyrene-maleic anhydride grafted chain segment, the styrene and maleic anhydride copolymer chains are anchored to the surface of the aromatic structure of the coal powder particles by π-π stacking. The acyl chloride groups formed by maleic anhydride chlorination condense with the hydroxyl groups of the sulfonated acetone-phenol condensation polymer. The grafted structure extends the long chain on the particle surface, generating a strong steric hindrance effect, preventing the particles from secondary aggregation.

[0021] 2. The auxiliary stabilizer is an oxidation-hydroxymethylation modified complex of lignin sulfonate and sodium humate. The modification process brings multiple functional improvements. During mechanical activation and oxidation modification, high-speed airflow pulverizes into ultrafine powder with a particle size of ≤5μm, increasing the specific surface area and improving the contact efficiency with the main dispersant. Ozone oxidation introduces polar groups such as carboxyl and hydroxyl groups, enhancing the charge of the molecular chain and assisting the main dispersant in maintaining particle dispersion through electrostatic repulsion. In the hydroxymethylation reaction, the hydroxymethyl groups introduced by formaldehyde form hydrogen bonds with the polar groups of the main dispersant, enhancing compatibility. Hydroxylation also causes the molecular chains to be slightly cross-linked, forming a stable network in the water-coal slurry and inhibiting particle settling.

[0022] 3. The primary dispersant preferentially adsorbs onto the surface of pulverized coal particles, achieving rapid dispersion through electrostatic repulsion and steric hindrance. The auxiliary stabilizer is modified to include additional polar groups, forming a second adsorption layer on the particle surface, strengthening electrostatic repulsion and providing additional steric hindrance. In terms of rheological properties, the grafted primary dispersant easily stretches at high shear rates, reducing friction within the system, and its viscosity decreases significantly with increasing shear rate. The auxiliary stabilizer inhibits particle aggregation at low shear rates, preventing a sudden increase in viscosity. Regarding storage stability, the oxidative-hydroxymethylation modification of the auxiliary stabilizer forms a colloidal protective layer in water, which synergizes with the steric hindrance of the primary dispersant to prevent particle aggregation during storage. DETAILED DESCRIPTION

[0023] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the embodiments described are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative efforts are within the scope of protection of the present invention.

[0024] The present invention provides a coal water slurry additive, which is composed of a main dispersant and an auxiliary stabilizer. The specific preparation steps are as follows:

[0025] Preparation of main dispersant

[0026] Phenol sulfonation: Mix phenol and concentrated sulfuric acid in a certain proportion, carry out sulfonation reaction at an appropriate temperature, and control the sulfonation degree at 62%-68%.

[0027] Preparation of sulfonated acetone-phenol polycondensate: condensing acetone and sulfonated phenol at 42-48° C. for 1.5 hours to generate a linear prepolymer; heating to 87-93° C., adding formaldehyde to carry out a cross-linking reaction for 2 hours, and adjusting the pH of the reaction system to 9.2-9.8; adding sodium bisulfite in an amount of 0.6%-0.9% by weight of the total reaction system to terminate the reaction, filtering, washing, and drying to obtain the sulfonated acetone-phenol polycondensate.

[0028] Preparation of polystyrene-maleic anhydride copolymer: Styrene and maleic anhydride are added to a toluene solvent (accounting for 55%-65% of the total mass of the reaction system) in a molar ratio of 3:1, and benzoyl peroxide (the amount is 1.3%-1.7% of the total mass of styrene and maleic anhydride) is added, and a free radical copolymerization reaction is carried out at 71-74°C to obtain a polystyrene-maleic anhydride copolymer.

[0029] Acid chloride treatment: The polystyrene-maleic anhydride copolymer is subjected to acid chloride treatment to convert 42%-48% of the carboxyl groups in the copolymer into acid chloride groups.

[0030] Grafting reaction: Add sulfonated acetone-phenol condensation product and chlorinated polystyrene-maleic anhydride in a mass ratio of 1: (0.35-0.45) to N,N-dimethylformamide, add zinc-aluminum composite oxide (the amount is 0.9-1.1wt% of the total mass), and react at 110-114°C for 4.0-4.8 hours to obtain the main dispersant.

[0031] Preparation of auxiliary stabilizers

[0032] Mechanical activation: Mix lignin sulfonate and sodium humate in a mass ratio of 3:1 and grind them into a particle size of ≤5μm using a high-speed airflow mill.

[0033] Oxidation modification: Place the mechanically activated material in an alkaline environment, adjust the pH to 10-11, introduce ozone for oxidation reaction, and control the oxidation degree at 15%-18%.

[0034] Hydroxymethylation reaction: add formaldehyde accounting for 8%-10% of the weight of lignin, react at 62-68°C for 1 hour, filter and wash to neutrality, and dry to obtain an auxiliary stabilizer.

[0035] The following are specific embodiments:

[0036] Example 1

[0037] Preparation of main dispersant

[0038] Phenol sulfonation: 1 mol of phenol, 0.65 mol of concentrated sulfuric acid, sulfonation at 80°C for 2 hours, sulfonation degree 65%.

[0039] Sulfonated acetone-phenol polycondensate: 1 mol of phenol (after sulfonation), 1 mol of acetone, and 2.2 mol of formaldehyde were condensed at 45°C for 1.5 hours, then heated to 90°C for cross-linking reaction for 2 hours. The pH was 9.5, and 0.75% sodium bisulfite was added to terminate the reaction to obtain a sulfonated acetone-phenol polycondensate with a weight-average molecular weight of 9500 Da.

[0040] Polystyrene-maleic anhydride copolymer: 3 mol of styrene, 1 mol of maleic anhydride, 60% toluene (accounting for the total mass of the reaction system), 1.5% benzoyl peroxide (accounting for the total mass of styrene and maleic anhydride), reaction at 73°C for 4 hours.

[0041] Acid chloride treatment: 45% of the carboxyl groups in the copolymer were converted into acid chloride groups.

[0042] Grafting reaction: sulfonated acetone-phenol condensation polymer and polystyrene-maleic anhydride are mixed in a mass ratio of 1:0.4, and N,N-dimethylformamide and 1.0 wt% zinc-aluminum composite oxide are added. The mixture is reacted at 112°C for 4.5 hours.

[0043] Preparation of auxiliary stabilizers

[0044] 30 g of lignin sulfonate and 10 g of sodium humate were ground by high-speed airflow to a particle size of ≤ 5 μm.

[0045] The pH was adjusted to 10.5, and ozone was introduced for oxidation, with an oxidation degree of 16.5%.

[0046] Add 3 g of formaldehyde, react at 65° C. for 1 hour, and dry to obtain an auxiliary stabilizer.

[0047] Preparation of additives: The main dispersant and the auxiliary stabilizer are mixed in a mass ratio of 1:0.3.

[0048] Example 2

[0049] Preparation of main dispersant

[0050] Phenol sulfonation: 1 mol of phenol, 0.65 mol of concentrated sulfuric acid, sulfonation at 80°C for 2 hours, sulfonation degree 65%.

[0051] Sulfonated acetone-phenol polycondensate: 1 mol of phenol (after sulfonation), 0.9 mol of acetone, and 2.2 mol of formaldehyde were condensed at 45°C for 1.5 hours, then heated to 90°C for cross-linking reaction for 2 hours. The pH was 9.5, and 0.75% sodium bisulfite was added to terminate the reaction to obtain a sulfonated acetone-phenol polycondensate with a weight-average molecular weight of 9500 Da.

[0052] Polystyrene-maleic anhydride copolymer: 3 mol of styrene, 1 mol of maleic anhydride, 60% toluene (accounting for the total mass of the reaction system), 1.5% benzoyl peroxide (accounting for the total mass of styrene and maleic anhydride), reaction at 73°C for 4 hours.

[0053] Acid chloride treatment: 45% of the carboxyl groups in the copolymer were converted into acid chloride groups.

[0054] Grafting reaction: sulfonated acetone-phenol condensation polymer and polystyrene-maleic anhydride are mixed in a mass ratio of 1:0.4, and N,N-dimethylformamide and 1.0 wt% zinc-aluminum composite oxide are added. The mixture is reacted at 112°C for 4.5 hours.

[0055] Preparation of auxiliary stabilizers

[0056] 30 g of lignin sulfonate and 10 g of sodium humate were ground by high-speed airflow to a particle size of ≤ 5 μm.

[0057] The pH was adjusted to 10.5, and ozone was introduced for oxidation, with an oxidation degree of 16.5%.

[0058] Add 3 g of formaldehyde, react at 65° C. for 1 hour, and dry to obtain an auxiliary stabilizer.

[0059] Preparation of additives: The mass ratio of main dispersant to auxiliary stabilizer is 1:0.25.

[0060] Example 3

[0061] Preparation of main dispersant

[0062] Phenol sulfonation: 1 mol of phenol, 0.65 mol of concentrated sulfuric acid, sulfonation at 80°C for 2 hours, sulfonation degree 65%.

[0063] Sulfonated acetone-phenol polycondensate: 1 mol of phenol (after sulfonation), 1.1 mol of acetone, and 2.4 mol of formaldehyde were condensed at 45°C for 1.5 hours, then heated to 90°C for cross-linking reaction for 2 hours. The pH was 9.5, and 0.75% sodium bisulfite was added to terminate the reaction to obtain a sulfonated acetone-phenol polycondensate with a weight-average molecular weight of 9500 Da.

[0064] Polystyrene-maleic anhydride copolymer: 3 mol of styrene, 1 mol of maleic anhydride, 60% toluene (accounting for the total mass of the reaction system), 1.5% benzoyl peroxide (accounting for the total mass of styrene and maleic anhydride), reaction at 73°C for 4 hours.

[0065] Acid chloride treatment: 45% of the carboxyl groups in the copolymer were converted into acid chloride groups.

[0066] Grafting reaction: sulfonated acetone-phenol condensation polymer and polystyrene-maleic anhydride are mixed in a mass ratio of 1:0.4, and N,N-dimethylformamide and 1.0 wt% zinc-aluminum composite oxide are added. The mixture is reacted at 112°C for 4.5 hours.

[0067] Preparation of auxiliary stabilizers

[0068] 30 g of lignin sulfonate and 10 g of sodium humate were ground by high-speed airflow to a particle size of ≤ 5 μm.

[0069] The pH was adjusted to 10.5, and ozone was introduced for oxidation, with an oxidation degree of 16.5%.

[0070] Add 3 g of formaldehyde, react at 65° C. for 1 hour, and dry to obtain an auxiliary stabilizer.

[0071] Preparation of additives: The mass ratio of main dispersant to auxiliary stabilizer is 1:0.45.

[0072] Example 4

[0073] Preparation of main dispersant

[0074] Phenol sulfonation: 1 mol of phenol, 0.65 mol of concentrated sulfuric acid, sulfonation at 80°C for 2 hours, sulfonation degree 65%.

[0075] Sulfonated acetone-phenol polycondensate: 1 mol of phenol (after sulfonation), 1 mol of acetone, and 2.2 mol of formaldehyde were condensed at 45°C for 1.5 hours, then heated to 90°C for cross-linking reaction for 2 hours. The pH was 9.5, and 0.75% sodium bisulfite was added to terminate the reaction to obtain a sulfonated acetone-phenol polycondensate with a weight-average molecular weight of 9500 Da.

[0076] Polystyrene-maleic anhydride copolymer: 3 mol of styrene, 1 mol of maleic anhydride, 60% toluene (accounting for the total mass of the reaction system), 1.5% benzoyl peroxide (accounting for the total mass of styrene and maleic anhydride), reaction at 73°C for 4 hours.

[0077] Acid chloride treatment: 45% of the carboxyl groups in the copolymer were converted into acid chloride groups.

[0078] Grafting reaction: sulfonated acetone-phenol condensation product and polystyrene-maleic anhydride are mixed in a mass ratio of 1:0.35, and N,N-dimethylformamide and 1.0 wt% zinc-aluminum composite oxide are added. The mixture is reacted at 112°C for 4.5 hours.

[0079] Preparation of auxiliary stabilizers

[0080] 30 g of lignin sulfonate and 10 g of sodium humate were ground by high-speed airflow to a particle size of ≤ 5 μm.

[0081] The pH was adjusted to 10.5, and ozone was introduced for oxidation, with an oxidation degree of 16.5%.

[0082] Add 3 g of formaldehyde, react at 65° C. for 1 hour, and dry to obtain an auxiliary stabilizer.

[0083] Preparation of additives: The main dispersant and the auxiliary stabilizer are mixed in a mass ratio of 1:0.3.

[0084] Example 5

[0085] It is basically the same as Example 1, except that:

[0086] The mass ratio of sulfonated acetone-phenol condensation polymer to polystyrene-maleic anhydride in the grafting reaction was 1:0.45.

[0087] The amount of formaldehyde used in the preparation of the auxiliary stabilizer is 10%.

[0088] The following is a comparative example

[0089] Comparative Example 1: The difference between this comparative example and Example 1 is that the mass ratio of the main dispersant to the auxiliary stabilizer in this comparative example is 1:0.15.

[0090] Comparative Example 2: The difference between this comparative example and Example 1 is that the auxiliary stabilizer is omitted in this comparative example, and only the main dispersant is used.

[0091] Comparative Example 3: This comparative example differs from Example 1 in that: in this comparative example, the auxiliary stabilizer is not subjected to oxidation-hydroxymethylation modification, and lignin sulfonate and sodium humate are directly mixed in a ratio of 3:1.

[0092] Experimental verification

[0093] Coal water slurry dispersion test

[0094] Test raw materials

[0095] Bituminous coal: fixed carbon content 65%, volatile matter 25%, moisture 8%, ash 2%.

[0096] Water: deionized water.

[0097] Additives: coal water slurry additives prepared in Examples 1-5 and Comparative Examples 1-3.

[0098] Preparation of water-coal slurry: according to the mass ratio of coal: water: additive of 65:34:1, coal, water and additive are added into the mixer and stirred at 1500r / min for 30 minutes to prepare water-coal slurry.

[0099] Dispersion test: Referring to GB / T29022-2021, the average particle size of coal particles in water-coal slurry was determined by light scattering method. The results are as follows:

[0100] Table 1

[0101]

[0102]

[0103] As can be seen from Table 1, the average particle size of the water-coal slurries of Examples 1-5 is between 14.6 and 15.5 μm, indicating that the additives have good dispersibility. In Comparative Example 1, the ratio of the main dispersant to the auxiliary stabilizer is too low, and the auxiliary stabilizer is insufficient, which cannot effectively cooperate with the main dispersant, resulting in poor coal particle dispersion and increased average particle size. In Comparative Example 2, the auxiliary stabilizer is omitted. It is difficult to maintain stable dispersion of coal particles with only the main dispersant, and the dispersibility is significantly reduced. The auxiliary stabilizer in Comparative Example 3 is unmodified, and its molecular structure has fewer active groups. The interaction with the main dispersant is weak, and the dispersion effect is unsatisfactory.

[0104] Coal water slurry stability test

[0105] The stability test was carried out in accordance with GB / T18856.4-2008. The prepared water-coal slurry was stored at room temperature for 7 days and its viscosity change rate was measured. The results are as follows:

[0106] Table 2

[0107]

[0108]

[0109] As can be seen from Table 2, the viscosity change rate of the water-coal slurries of Examples 1-5 ranged from 4.13% to 4.92%, indicating good stability. Due to the insufficient proportion of auxiliary stabilizer in Comparative Example 1, the aggregation of coal particles could not be effectively suppressed during storage, resulting in a significant increase in viscosity. Comparative Example 2 lacked an auxiliary stabilizer, and the stabilizing effect of the primary dispersant was limited, resulting in the worst water-coal slurry stability. The auxiliary stabilizer in Comparative Example 3 was unmodified, and its steric hindrance and electrostatic repulsion were weak, making it difficult to maintain the stability of the water-coal slurry. The viscosity change rate was higher than that of the examples.

[0110] Throughout this specification, references to terms such as "one embodiment," "example," or "specific example" indicate that the specific features, structures, materials, or characteristics described in conjunction with that embodiment or example are included in at least one embodiment or example of the present invention. In this specification, schematic representations of these terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in any one or more embodiments or examples.

[0111] The preferred embodiments of the present invention disclosed above are intended only to help illustrate the present invention. These preferred embodiments do not exhaustively describe all details, nor do they limit the present invention to the specific embodiments described. Obviously, many modifications and variations are possible based on the content of this specification. These embodiments are selected and described in detail in this specification to better explain the principles and practical applications of the present invention, thereby enabling those skilled in the art to better understand and utilize the present invention. The present invention is limited only by the claims and their full scope and equivalents.

Claims

1. A coal water slurry additive, characterized in that: The invention is composed of a main dispersant and an auxiliary stabilizer; the main dispersant is polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, the auxiliary stabilizer is an oxidation-hydroxymethylation modified complex of lignin sulfonate and sodium humate, and the mass ratio of the main dispersant to the auxiliary stabilizer is 1:(0.25-0.45).

2. The coal water slurry additive according to claim 1, characterized in that The polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer is prepared by reacting phenol, acetone, and formaldehyde, wherein the molar ratio of the phenol, acetone, and formaldehyde is 1:(0.9-1.1):(2.1-2.4), and the phenol is pre-sulfonated with concentrated sulfuric acid to a degree of sulfonation of 62%-68%. The weight-average molecular weight of the sulfonated acetone-phenol condensation polymer is 8500-11500 Da.

3. The coal water slurry additive according to claim 2, characterized in that The preparation method of the sulfonated acetone-phenol polycondensate comprises: condensing acetone and sulfonated phenol at 42-48° C. for 1.5 hours to generate a linear prepolymer; heating to 87-93° C., adding formaldehyde to carry out a cross-linking reaction for 2 hours, and adjusting the pH value of the reaction system to 9.2-9.8; terminating the reaction by adding sodium bisulfite, a reaction terminator, accounting for 0.6%-0.9% of the total mass of the reaction system; and finally filtering, washing, and drying to obtain the product.

4. The coal water slurry additive according to claim 3, characterized in that In the polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, the polystyrene-maleic anhydride copolymer is prepared by free radical copolymerization of styrene and maleic anhydride, the molar ratio of styrene to maleic anhydride is 3:1, the reaction is carried out in a toluene solvent accounting for 55%-65% of the total mass of the reaction system, the initiator is benzoyl peroxide, the amount used is 1.3%-1.7% of the total mass of styrene and maleic anhydride, and the reaction temperature is 71-74°C.

5. The coal water slurry additive according to claim 4, characterized in that: The polystyrene-maleic anhydride copolymer needs to be subjected to chlorination treatment to convert 42%-48% of the carboxyl groups in the copolymer into chlorinated groups.

6. The coal water slurry additive according to claim 1, characterized in that In the polystyrene-maleic anhydride grafted sulfonated acetone-phenol condensation polymer, the mass ratio of the sulfonated acetone-phenol condensation polymer to the polystyrene-maleic anhydride is 1:(0.35-0.45). In the aprotic solvent N,N-dimethylformamide, a zinc-aluminum composite oxide is used as a bimetallic catalyst to catalyze the condensation of the hydroxyl-terminated sulfonated acetone-phenol condensation polymer with the acyl chloride group. The amount of the zinc-aluminum composite oxide is 0.9-1.1 wt % of the total mass of the sulfonated acetone-phenol condensation polymer and the polystyrene-maleic anhydride.

7. The coal water slurry additive according to claim 6, characterized in that The grafting reaction temperature is 110-114° C., and the reaction time is 4.0-4.8 hours.

8. The coal water slurry additive according to claim 1, characterized in that: The preparation method of the auxiliary stabilizer comprises: Mechanical activation step: mixing lignin sulfonate and sodium humate, and crushing them by a high-speed airflow mill to make the mixed material particle size ≤5μm; Oxidation modification step: Place the mechanically activated material in an alkaline environment, adjust the system pH to 10-11, introduce ozone for oxidation reaction, and control the oxidation degree at 15%-18%; Hydroxymethylation reaction step: add formaldehyde accounting for 8%-10% of the weight of lignin to the material after oxidative modification, react at 62-68° C. for 1 hour, filter and wash to neutrality, and dry to obtain an auxiliary stabilizer.

9. The coal water slurry additive according to claim 8, characterized in that: In the auxiliary stabilizer, the mass ratio of lignin sulfonate to sodium humate is 3:1.